Algunos cambios léxico-semánticos en el español de América: una aproximación a través de Elegías de Varones Ilustres de Indias (1589) de Juan de Castellanos - Jáimez, Rita (2015)
This paper studies the lexical-semantic changes suffered by apechugar [undertake], atarantado [astounded, lightheaded, thoughless], baraja [quarrel], blanca [money], desayunarse [to get astonishing news], pelar [to get someone’s money], pluma [money] in several Spanish-speaking American countries (e.g. Colombia, Argentina, Uruguay and others) with emphasis on Venezuela. These words were used by Juan de Castellanos in his Elegías de Varones Ilustres de Indias (1589). The study verifies the evolution of these voices through lexicographical important books. The investigation concludes that, after 500 years, (i) the examined lexis stay in America, (ii) new entities have been produced from these vocabularies, (iii) the terms have changed their meaning, what giving them character own to the American Spanish.